Cardiac magnetic resonance and computed tomography angiography for clinical imaging of stable coronary artery disease. Diagnostic classification and risk stratification - Korosoglou, Grigorios; Giusca, Sorin; Gitsioudis, Gitsios; Erbel, Christian; Katus, Hugo A. (Frontiers in Physiology, 2014)
Despite advances in the pharmacologic and interventional treatment of coronary artery disease (CAD), atherosclerosis remains the leading cause of death in Western societies. X-ray coronary angiography has been the modality of choice for diagnosing the presence and extent of CAD. However, this technique is invasive and provides limited information on the composition of atherosclerotic plaque. Coronary computed tomography angiography (CCTA) and cardiac magnetic resonance (CMR) have emerged as promising non-invasive techniques for the clinical imaging of CAD. Hereby, CCTA allows for visualization of coronary calcification, lumen narrowing and atherosclerotic plaque composition. In this regard, data from the CONFIRM Registry recently demonstrated that both atherosclerotic plaque burden and lumen narrowing exhibit incremental value for the prediction of future cardiac events. However, due to technical limitations with CCTA, resulting in false positive or negative results in the presence of severe calcification or motion artifacts, this technique cannot entirely replace invasive angiography at the present time. CMR on the other hand, provides accurate assessment of the myocardial function due to its high spatial and temporal resolution and intrinsic blood-to-tissue contrast. Hereby, regional wall motion and perfusion abnormalities, during dobutamine or vasodilator stress, precede the development of ST-segment depression and anginal symptoms enabling the detection of functionally significant CAD. While CT generally offers better spatial resolution, the versatility of CMR can provide information on myocardial function, perfusion and viability, all without ionizing radiation for the patients. Technical developments with these 2 non-invasive imaging tools and their current implementation in the clinical imaging of CAD will be presented and discussed herein.